Animal Reservoirs of Zoonotic Tungiasis in Endemic Rural Villages of Uganda - Mutebi, Francis (PLoS Negl Trop Dis, 2015)
BACKGROUND: Animal tungiasis is believed to increase the prevalence and parasite burden in humans. Animal reservoirs of Tunga penetrans differ among endemic areas and their role in the epidemiology of tungiasis had never been investigated in Uganda. METHODS AND FINDINGS: To identify the major animal reservoirs of Tunga penetrans and their relative importance in the transmission of tungiasis in Uganda, a cross sectional study was conducted in animal rearing households in 10 endemic villages in Bugiri District. T. penetrans infections were detected in pigs, dogs, goats and a cat. The prevalences of households with tungiasis ranged from 0% to 71.4% (median 22.2) for animals and from 5 to 71.4% (median 27.8%) for humans. The prevalence of human tungiasis also varied among the population of the villages (median 7%, range 1.3–37.3%). Pig infections had the widest distribution (nine out of 10 villages) and highest prevalence (median 16.2%, range 0–64.1%). Pigs also had a higher number of embedded sand fleas than all other species combined (p<0.0001). Dog tungiasis occurred in five out of 10 villages with low prevalences (median of 2%, range 0–26.9%). Only two goats and a single cat had tungiasis. Prevalences of animal and human tungiasis correlated at both village (rho = 0.89, p = 0.0005) and household (rho = 0.4, p<0.0001) levels. The median number of lesions in household animals correlated with the median intensity of infection in children three to eight years of age (rho = 0.47, p<0.0001). Animal tungiasis increased the odds of occurrence of human cases in households six fold (OR = 6.1, 95% CI 3.3–11.4, p<0.0001). CONCLUSION: Animal and human tungiasis were closely associated and pigs were identified as the most important animal hosts of T. penetrans. Effective tungiasis control should follow One Health principles and integrate ectoparasites control in animals.